Collaboration Converts Cardiac Catastrophe During Living Donor Kidney Recipient Surgery to Long Term Success. (July 2018) - Mai, Martin
Abstract : Background: Cardiovascular disease is more common in CKD and evaluation of perioperative risk for potential kidney transplant recipients is essential to reduce adverse postoperative complications. Collaborative work between multiple disciplines better prepares recipients for surgery and can mitigate adverse outcomes. A case presenting multidisciplinary teamwork to offset cardiac complications in setting of living donor (LD) recipient surgery is presented. Case: 44 y/o man with diabetes mellitus type 1 and ESRD on hemodialysis for 1 year is evaluated for LD kidney transplant. He has history of myocardial infarct 5 years earlier s/p stent and stroke 5 years ago without sequelae. He has no symptoms of cardiovascular disease. Preoperative Echo shows EF 55% without pulmonary hypertension. Cardiolite nuclear medicine stress test reveals small fixed apical lateral defect suggestive of infarct without ischemia. Cardiac catheterization demonstrates left anterior descending (LAD) mid 80% stenosis, circumflex with 70-80% narrowing and right coronary artery (RCA) with proximal widely patent stent and distal 20-30% lesion. He had stents placed in LAD and circumflex (bare metal). He is cleared for LD transplant. He is taken to surgery 4 months later; undergoing successful anesthesia induction and the living donor kidney is anastomosed to recipient vein followed by sudden drop in BP, not responding to fluids. TEE shows EF 10%. The living donor kidney is detached from recipient vein, flushed and packaged per UNOS protocol. The team decides to notify the donor after anesthesia recovery and discuss option of offering the kdiney to the deceased donor list (subsequently donor concurred with this plan). Cardiology is consulted. Transplant Surgery closes wound. Recipient is emergently taken from operating room to heart cath lab (with Anesthesia in attendance) where an occluded LAD is found in addition to distal 90% circumflex and 75-80% RCA lesions. LAD occlusion is restented (bare metal stent) and IABP is placed. Patient is taken to intensive care unit where Critical Care Service provides support and stabilizes recipient. A huddle between Critical Care, Cardiology, Transplant Surgery, Anesthesia and Transplant Nephrology discussed options, relaying these to donor and recipient families. In the morning IABP is removed and recipient is cleared for transplant (repeat EF is 30%). Living donor kidney is successfully placed with slow but persistent fall in creatinine without need for dialysis on discharge. 10 years later, his Cr is 1.7mg/dl with measured iothalmate clearance of 58 ml/min and 490 mg proteinuria. Discussion: Despite careful evaluation, unexpected postoperative complications may adversely affect kidney transplant surgery. Quick teamwork to address the problem mitigates risk. The framework of multidisciplinary care in this example of a cardiac complication during recipient surgery of a living donor kidney transplant enabled successful transplant and long term success.